LIBRAS in the sexual education of the deaf person (Research, Society and Development, 2020)
This study addresses the social vision and stigma of sexuality of deaf people. According to Dizeu and Caporali (2005), there is a need to promote the use of LIBRAS both in the school and family context still in childhood seeking a better relationship between them, because this interaction would be more productive, collaborating in the construction of the identity of the deaf, besides preventing damage and disorders by facilitating access to an informative and comprehensive sexual education, considering the importance of this in the development of sexuality of the individual, emphasizing their rights to experience sexual pleasure. A literature review was used based on the terms deafness, sexuality, sexual education of the deaf, deaf culture. As a result of the search, 26 researches were obtained, among them only 8 directly addressed the sexual education of the deaf. As a result of the study, it was observed that there is a limited view about the deaf, making it impossible to access the discoveries of their identity, being placed as mentally incapable of a healthy development of notions about their own subjectivity and the world, hindering the process of social inclusion. When it comes to inclusion and access to information, human sexuality should not be discarded. It is necessary to understand that deaf subjects share a culture evidenced through their own language and the linguistic issue should not be an impediment in their social development.